The Influence of Employee Benefits Preferences on The Job Retention of Generation Y and Z Employees at PT X Information Technology Company in Indonesia - Susendi Widjaya; Tongam Sirait (Al-Makki Publisher, 2024)
The COVID-19 pandemic has changed the landscape of the labor market in Indonesia, especially in the fast-growing information technology sector. Generation Y and Z employees have high expectations for workplace welfare, including employee benefits. This study aims to analyze the effect of employee benefits preferences, both direct financial compensation, indirect financial compensation, and non-financial compensation on the job retention of generation Y and Z employees at PT X. This research uses a descriptive quantitative approach with a survey method. The sample consisted of 88 respondents randomly selected from a total population of 727 employees. Data were collected through questionnaires and analyzed using validity and reliability tests, as well as regression analysis. The results showed that all types of compensation have a significant effect on job retention. Direct financial compensation exerts the greatest influence, followed by non-financial compensation. Employees who are satisfied with employee benefits tend to be more loyal and have a lower desire to change jobs. Employee benefits preference has a positive impact on the retention of generation Y and Z employees at PT X. To increase retention, companies need to pay attention and improve the quality of employee benefits offered. This research provides input for companies in designing more effective human resource management strategies.